Federal Court Cases: Integrated Data Base, 2002 ([Verlag nicht ermittelbar], 2004)
The purpose of this data collection is to provide an official public record of the business of the federal courts. The data originate from district and appellate court offices throughout the United States. Information was obtained at two points in the life of a case: filing and termination. The termination data contain information on both filing and terminations, while the pending data contain only filing information.